Kritiske perspektiver i helsefagene Utdanning, yrkespraksis og forskning - Feiring, Marte; Ruud Knutsen, Ingrid; I. Juritzen, Truls; Larsen, Kristian (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Professional criticism and reflection are important elements in all health science practices and knowledge development. This anthology presents a wide range of critical perspectives on health care and health science, aimed at challenging and encouraging the reader for critical reflection.